The Impact of Industrial Agglomeration on Labor Misallocation in East Java - Wisnu Purnomo; Martha Ranggi Primanthi (East Java Economic Journal, 2025)
Agglomeration is believed to offer various advantages to firms located within its area. One such benefit is the potential reduction in labor misallocation. However, theoretical expectations do not always align with real-world practices. This study aims to analyze the impact of industrial agglomeration areas on the degree of labor misallocation in East Java by utilizing panel data from the Large and Medium Manufacturing Industry Survey (IBS) for the period 2010–2015. The analysis employs a fixed effects panel regression method. The findings reveal that firms located within agglomeration areas experience a labor misallocation level 2.52 times higher than those outside such areas. Additionally, a 1% increase in the number of workers leads to a 0.122% increase in labor misallocation. Exporting firms tend to exhibit a higher level of misallocation compared to non-exporting firms, by 1.926 points. Moreover, the study finds that a higher Herfindahl-Hirschman Index (HHI) among firms also contributes to greater labor misallocation. Specifically, a one-point increase in the HHI is associated with a 0.7% rise in labor misallocation